Cutting the long branches: Consilience as a path to unearth the evolutionary history of Gnetales - Coiro, Mario; Roberts, Emily A.; Hofmann, Christa-Ch.; Seyfullah, Leyla J. (Frontiers in Ecology and Evolution, 2022)
The Gnetales are one of the most fascinating groups within seed plants. Although the advent of molecular phylogenetics has generated some confidence in their phylogenetic placement of Gnetales within seed plants, their macroevolutionary history still presents many unknowns. Here, we review the reasons for such unknowns, and we focus the discussion on the presence of ‘long branches’ both in their molecular and morphological history. The increased rate of molecular evolution and genome instability as well as the numerous unique traits (both reproductive and vegetative) in the Gnetales have been obstacles to a better understanding of their evolution. Moreover, the fossil record of the Gnetales, though relatively rich, has not yet been properly reviewed and investigated using a phylogenetic framework. Despite these apparent blocks to progress we identify new avenues to enable us to move forward. We suggest that a consilience approach, involving different disciplines such as developmental genetics, paleobotany, molecular phylogenetics, and traditional anatomy and morphology might help to ‘ break’ these long branches, leading to a deeper understanding of this mysterious group of plants.